2022
DOI: 10.3389/fmolb.2022.824989
|View full text |Cite
|
Sign up to set email alerts
|

Mastoparans: A Group of Multifunctional α-Helical Peptides With Promising Therapeutic Properties

Abstract: Biologically active peptides have been attracting increasing attention, whether to improve the understanding of their mechanisms of action or in the search for new therapeutic drugs. Wasp venoms have been explored as a remarkable source for these molecules. In this review, the main findings on the group of wasp linear cationic α-helical peptides called mastoparans were discussed. These compounds have a wide variety of biological effects, including mast cell degranulation, activation of protein G, phospholipase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 147 publications
0
23
0
3
Order By: Relevance
“…Hymenoptera venoms consist of a complex mixture of chemically or pharmacologically bioactive components including phospholipases, hyaluronidases and mastoparans [ 69 ]. Mastoparans, a group of alpha-helical peptides, appear to be the most promising for pharmacological activities [ 37 ] since they are able to penetrate into cells and bind DNA [ 70 ]. Melectin, an antimicrobial peptide from the venom of the cleptoparasitic bee Melecta albifrons , does not exhibit sequence homology with other wasp venom peptides.…”
Section: Results Of Literature Searchmentioning
confidence: 99%
“…Hymenoptera venoms consist of a complex mixture of chemically or pharmacologically bioactive components including phospholipases, hyaluronidases and mastoparans [ 69 ]. Mastoparans, a group of alpha-helical peptides, appear to be the most promising for pharmacological activities [ 37 ] since they are able to penetrate into cells and bind DNA [ 70 ]. Melectin, an antimicrobial peptide from the venom of the cleptoparasitic bee Melecta albifrons , does not exhibit sequence homology with other wasp venom peptides.…”
Section: Results Of Literature Searchmentioning
confidence: 99%
“…Nọc độc của những loài côn trùng và lưỡng cư là một trong những nguồn quan trọng cung cấp các AMP tiềm năng [1][2][3]. Trong số đó, ong bắp cày được nghiên cứu nhiều nhất [4][5][6]. Tác dụng kháng khuẩn tốt đối với nhiều vi sinh vật gây bệnh bao gồm cả một số chủng kháng thuốc trên lâm sàng và khả năng gây tán huyết thấp đã làm cho các hợp chất này trở thành những ứng cử viên tiềm năng để phát triển thành thuốc chống nhiễm trùng [3].…”
Section: ________unclassified
“…Khoảng 40 chuỗi peptid từ nọc ong bắp cày sống theo đàn và 6 chuỗi từ những loài đơn độc đã được mô tả. Kết quả nghiên cứu đã chứng tỏ các peptid thuộc họ này có nhiều tác dụng sinh học như kích hoạt protein G, kích hoạt phospholipase A2, C và D, giải phóng serotonin và insulin, kháng khuẩn, tán huyết, chống ung thư, thúc đẩy sự gia tăng Ca 2+ nội bào nhằm điều chỉnh quá trình giao tiếp giữa các tế bào [6].…”
Section: ________unclassified
See 1 more Smart Citation
“…In contrast, Mastoparan-L was only active against Gram-positive bacteria and some strains of Brucella abortus, while having limited effect on probiotics. 35 Furthermore, in the previous report, we compared the antimicrobial properties of nano-titanium dioxide (TiO 2 -NP), and nano-zinc oxide (ZnO NP), with two synthetic peptides (MP-B and Indolicidin) against MDR strains of P. aeruginosa, and hypervirulent strains of K. pneumoniae. 36 Nevertheless, it was found that combining antibiotics with MP-B at the sub-MIC level circumvented the resistance phenomenon and significantly reduced antibiotic dose.…”
Section: Introductionmentioning
confidence: 99%